2006
DOI: 10.1017/s0033291706008269
|View full text |Cite
|
Sign up to set email alerts
|

Indicators of fetal growth and bipolar disorder: a Danish national register-based study

Abstract: None of the indicators of fetal growth under study could be identified as risk factors for bipolar disorder, suggesting that the etiologies of schizophrenia and bipolar disorder, at least in part, are different.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(23 citation statements)
references
References 27 publications
1
20
1
1
Order By: Relevance
“…The lack of association between birth weight and BPD has been seen in three previous studies (Øgendahl et al, 2006; Bain et al, 2000; Eaton et al, 2000). Similarly, three previous population-based studies (Nosarti et al, 2012; Eaton et al, 2000; Øgendahl et al, 2006) have examined the association between gestational age and BPD and found no association. However, these negative findings are in contrast to a study showing increased risk of BPD in children born preterm (Nosarti et al, 2012).…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…The lack of association between birth weight and BPD has been seen in three previous studies (Øgendahl et al, 2006; Bain et al, 2000; Eaton et al, 2000). Similarly, three previous population-based studies (Nosarti et al, 2012; Eaton et al, 2000; Øgendahl et al, 2006) have examined the association between gestational age and BPD and found no association. However, these negative findings are in contrast to a study showing increased risk of BPD in children born preterm (Nosarti et al, 2012).…”
Section: Discussionmentioning
confidence: 63%
“…Findings of the studies on gestational age and on birth weight adjusted for gestational age have been inconsistent. A Swedish study (Nosarti et al, 2012) found preterm birth to be associated with increased risk of BPD, while two Danish studies (Øgendahl et al, 2006; Eaton et al, 2000) failed to show similar associations. A Danish study (Laursen et al, 2007) showed increased risk in preterm children born small for gestational age (SGA) whereas SGA was not associated with BPD in two Swedish studies (Nosarti et al, 2012; Hultman et al, 1999) and a Scottish study (Bain et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations